Intracranial Lipoma: A Rare Variant of Brain Tumor - Singh, Anish M; Adhikari, Rupendra B; Sah, Hemant; Shrestha, Prabia (Nepal Journal of Neuroscience, 2016)
Nepal Journal of Neuroscience 12:72, 2015